Pengaruh Dukungan Sosial terhadap Kondisi Kecemasan dalam Menghadapi Pensiun (Post Power Syndrom) - Ikawati Ikawati; Tri Gutomo (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2014)
This research is done to know the influence of social support on anxiety condition having retirement (Post Power Syndrome). This research is a correlational study. The research location is choosen purposively as the area with highest aged prevalention (BPS, 2010). Based on that consideration, Yogyakarta Special Teritory, is choosen as research location. Research subjects are also choosen purposifely, with category that research subject are already retired from work, more than 60 years of age, men or women, still have living partner and family, and highschool educated, with retirement grant two to three million a month. Based on the consideration to the research subject, choosen 30 respondents. The objects of this research are social support and the anxiety of having retirement (Post Power Syndrome). Data gathered through guided interview and observation techniques, and analysed with regression technique. The result shows that there is enfluence of social support on anxiety condition, having retirement. The enfluence can be seen from the degree of effective contribution towards anxiety condition having retirement (Post Power Syndrome), as 72 per cent high. That means there are other variables or factors enfluence the anxiety condition, as big as 28 per cent. Other enfluencial factors can be seen from the degree of related contribution of each variable, they are an emotional support (8,881 per cent), information suppror (17,297 per cent), instrumental support (8,358 per cent), and evaluation support (73, 297 per cent). Refer to the result, it is recommended to The Ministry of Social Affairs, especially the Diractory of Aged Service, that for the sake of enhancing aged social welfare, especially for those having retired or is retired, it needs programs that can commit and empower aged through their thought, idea, and advice to prevent aged from being anxieted of having retired (Post Pwer Syndrome), or through creating new cariers to develop beneficial desire and hobby.